Modified T-type topology of three-phase multi-level inverter for photovoltaic systems - Abderrahmane Ouchatti; Redouane Majdoul; Ahmed Moutabir; Abderrahim Taouni; Abdelouahed Touati (Institute of Advanced Engineering and Science, 2022)
In this article, a three-phase multilevel neutral-point-clamped inverter with a modified t-type structure of switches is proposed. A pulse width modulation (PWM) scheme of the proposed inverter is also developed. The proposed topology of the multilevel inverter has the advantage of being simple, on the one hand since it does contain only semiconductors in reduced number (corresponding to the number of required voltage levels), and no other components such as switching or flying capacitors, and on the other hand, the control scheme is much simpler and more suitable for variable frequency and voltage control. The performances of this inverter are analyzed through simulations carried out in the MATLAB/Simulink environment on a three-phase inverter with 9 levels. In all simulations, the proposed topology is connected with R-load or RL-load without any output filter.